2011
DOI: 10.3945/ajcn.110.003871
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response effects of omega-3 fatty acids on triglycerides, inflammation, and endothelial function in healthy persons with moderate hypertriglyceridemia

Abstract: Background: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been shown to reduce cardiovascular mortality at a dose of '1 g/d. Studies using higher doses have shown evidence of reduced inflammation and improved endothelial function. Few studies have compared these doses. Objective: The objective of this study was to compare the effects of a nutritional dose of EPA+DHA (0.85 g/d) with those of a pharmaceutical dose (3.4 g/d) on serum triglycerides, inflammatory markers, and endothelial function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
166
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(189 citation statements)
references
References 63 publications
16
166
3
4
Order By: Relevance
“…This finding has been previously reported, although primarily in individuals with hypertriglyceridemia. 16,17 Our subjects, on the other hand, had normal serum triglyceride levels. We also observed a significant increase in HDL cholesterol following Lovaza administration (8% in women receiving Lovaza alone and 16% in those receiving the combination of Lovaza and Ral).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has been previously reported, although primarily in individuals with hypertriglyceridemia. 16,17 Our subjects, on the other hand, had normal serum triglyceride levels. We also observed a significant increase in HDL cholesterol following Lovaza administration (8% in women receiving Lovaza alone and 16% in those receiving the combination of Lovaza and Ral).…”
Section: Discussionmentioning
confidence: 99%
“…This is at variance with other reports in the literature where Lovaza was reported to either cause no change 16 or a minimal increase (1-3%) in HDL cholesterol. 17 IGF-I is a potent mitogen for breast cancer and has been postulated to be involved in mammary carcinogenesis, tumor progression and metastasis. 18,19 Elevated levels of circulating IGF-I have been shown to be a significant risk factor for premenopausal breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The reactive hyperemia index, as a marker of flowmediated vasodilatation, was measured with the EndoPAT system (Itamar Medical Ltd., Franklin, MA), which assesses the capillary blood refill to finger tips after a 5-min occlusion of the forearm with a cuff inflated to 50 mmHg above the participant's resting systolic blood pressure and expressed as a ratio of the blood flow in the opposite arm (18). Diet records were analyzed using a computer program (ESHA Food Processor SQL version 10.9; ESHA, Salem, OR) based on U.S. Department of Agriculture data (19) and international GI tables (20) using the bread scale (where bread = 100; for the glucose scale, bread scale values were multiplied by 0.71) (21) (Supplementary Table 1).…”
Section: Biochemical and Dietary Analysesmentioning
confidence: 99%
“…Several intervention studies have shown variable results (78)(79)(80) . A well-powered study with 324 participants investigating the effect of LC n-3 PUFA supplementation showed favourable effects on circulating CRP and IL-6 concentrations, when compared with sunflower oil (78) .…”
Section: Human Perspectivesmentioning
confidence: 99%